Nodal anatomical study in some Rubiaceae - Patil, C R; Patil, D A (Journal of Experimental Sciences, 2012)
Anatomies of the nodes belonging to 20 species 11 genera of the family Rubiaceae are investigated. Of these, 16 species exhibited trilacunar, three-traced supply to the leaves. In case of Canthium coromandelicum, Gardenia latifolia, G. longistyla, the nodes show five-lacunar, five-traced supply. In Luculia gratissiuma, they are unilacunar, one-traced. Variation in emergence of median and lateral traces however, is observed. It is the median trace that departs first in 15 species; whereas in the rest others lateral traces emerge earlier, except Luculia gratissima wherein the node being unilacunar, one-traced only. The stipule usually receives vascular supply from the lateral traces. However in Luculia gratissima, it is the solitary trace that bears vascular supply to them. The present authors are inclined to regard the unilacunar, one-traced supply basic for the family Rubiaceae, whereas others are thought later attainments.